UPAYA PENINGKATAN NASIONALISME MELALUI PENDIDIKAN BELA NEGARA DI ERA DIGITALISASI PADA PENGURUS ORGANISASI SISWA INTRA SEKOLAH ( OSIS) SMA NEGERI 2 SLAWI: UPAYA PENINGKATAN NASIONALISME MELALUI PENDIDIKAN BELA NEGARA DI ERA DIGITALISASI PADA PENGURUS ORGANISASI SISWA INTRA SEKOLAH ( OSIS) SMA NEGERI 2 SLAWI - Adam, David Bani (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2025)
The student organization in the school is the Intra-School Student Organization (OSIS). Student Council has the function of coaching and developing students to prepare cadres to continue the nation's struggle by providing skills, leadership, idealism, patriotism, personality, and noble character, so efforts are needed to foster a spirit of nationalism through National Defense Education. One of them is the Slawi 2 State Senior High School Student Council. In recent developments, several extracurricular activities at SMA Negeri 2 Slawi have made many proud achievements, however, soft skills need to be balanced in the form of insight into nationalism. Therefore, it is necessary to instill nationalism through State Defense Education in the era of digitalization for OSIS administrators in the form of Community Service (PKM) activities. PKM activities were carried out at SMA Negeri 2 Slawi with the target participants being the OSIS board. Training activities are in the form of an understanding of defending the country, outreach about anti-bullying, and limits on the use of social media. With this PKM activity it is hoped that the OSIS board can carry out its functions and roles properly and become the front guard in realizing the school's vision and mission.